Structure of Superdeformed Rotational Bands in A 150 Mass Region - Kotb, Mahmoud; Khalaf, A.M.; Altalhi, F.A. (JOURNAL OF ADVANCES IN PHYSICS, 2015)
The structure of superdeformed rotational bands (SDRB’s) in A 150 mass region are studied by using the Harris three parameter expansion and the incremental alignment. The bandhead spins Io have been determined with best fit procedure in order to obtain a minimum root mean square deviation between the calculated and the experimental dynamical moments of inertia. The kinematic moment of inertia has been calculated as a function of rotational frequency and compared to the corresponding experimental ones by assuming three spin values Io - 2 , Io , Io + 2. The transition energies and the variation of the moments of inertia as a function of rotational frequency have been calculated. The agreement between theory and experiment are excellent. The identical bands of SDRB’s with Î”I = 2 staggering in 148Gd (SD6) and 149Gd (SD1) are investigated. Also the presence of Î”I = 2 staggering effect in the yrast bands of 147Eu and 150Tb has been examined.